2020
DOI: 10.1177/2473011420916139
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Drilling for Osteochondral Lesion of the Talus in Juvenile Patients

Abstract: Background: Retrograde drilling (RD) is generally used for treating osteochondral lesion of the talus (OLT) with a stable osteochondral fragment and nearly normal articular cartilage surface. Previous studies that included participants of various ages have reported good clinical results. This study aimed to clarify the clinical outcomes of RD for OLT in juvenile patients whose bone-forming ability and physical activity might affect the healing process. Methods: This retrospective study included 8 juvenile pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…A simplified pooling method was performed for 3 studies reporting clinical outcomes after treatment with RD. 9 , 24 This yielded a pooled success rate of 95% (95% CI: 78%-99%) for a total of 22 patients. Two studies reported separate results for lesions with and without a history of trauma, 9 , 24 yielding a success rate of 86% (95% CI: 47%-97%) for traumatic lesions and 100% (95% CI: 65%-100%) for lesions without a history of trauma, for a total of 7 and 7 lesions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A simplified pooling method was performed for 3 studies reporting clinical outcomes after treatment with RD. 9 , 24 This yielded a pooled success rate of 95% (95% CI: 78%-99%) for a total of 22 patients. Two studies reported separate results for lesions with and without a history of trauma, 9 , 24 yielding a success rate of 86% (95% CI: 47%-97%) for traumatic lesions and 100% (95% CI: 65%-100%) for lesions without a history of trauma, for a total of 7 and 7 lesions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…They performed retrograde drilling only in the case of intact overlaying cartilage identified in arthroscopy. Another series of eight patients (mean age 14.9 years) who were treated with retrograde drilling were also reported to have significant clinical improvements (according to the American Orthopaedic Foot and Ankle Society ankle hind-foot score and ankle activity score) [ 24 ]. The OCLTs treated in the above study had a cartilage status of ICRS stage 0 or 1.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports of good clinical outcomes following ankle arthroscopy and retrograde drilling [ 4 , 7 , 8 ]. However, this technique is reserved for OCLTs with intact overlaying cartilage [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Operative therapy options of OCLTs in the paediatric and adolescent population vary; there is a lack of internationally accepted treatment guidelines. For low-stage OCLTs, good clinical results have been reported after arthroscopic treatment with bone marrow stimulation (BMS) techniques, fragment fixation, and retrograde drilling [ 3 8 ]. However, relatively high re-operation rates due to treatment failure have also been reported [ 9 ].…”
Section: Introductionmentioning
confidence: 99%